Diversitas Jenis Mangrove di Pesisir Pantai Kawangu Kabupaten Sumba Timur sebagai Sumber Belajar Booklet - Ataluda, Ningsih Rambu; Ina, Anita Tamu; Makatita, Audrey Louise; Matulessy, Yoin Meissy (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
Abstract: The purpose of this study was to describe the diversity of mangrove species on the coast of Kawangu Beach, Kawangu Village, East Sumba Regency and make the result of research as a source of learning biology in the form of booklets. The sampling technique used in this study is purposive sampling technique and the sampling method uses a method that is combined between the line method and the plot line method as many as two observation stations. The results of the study found consist of 4 orders, 5 families, 6 genera, 6 species and as many as 692 individuals, namely: Avicennia alba, Ceriops tagal, Rhizophora stylosa, Lumnitzera racemosa, Sonneratia alba, Xylocarpus moluccensis. The diversity index of mangrove species on the coast of Kawangu Beach is 1.671 classified in the medium category. The results of the booklet validation test by validator I were 91.67% and validator II was 95%. This value indicates that the booklet is feasible to be utilized as a biology learning resource.